2008
DOI: 10.1118/1.2826557
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical model-based segmentation of the organs of sight on CT images

Abstract: Segmentation of organs of sight such as the eyeballs, lenses, and optic nerves is a time consuming task for clinicians. The small size of the organs and the similar density of the surrounding tissues make the segmentation difficult. We developed a new algorithm to segment these organs with minimal user interaction. The algorithm needs only three seed points to fit an initial geometrical model to start an effective segmentation. The clinical evaluation shows that the output of our method is useful in clinical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 6 publications
0
42
0
Order By: Relevance
“…Parametric deformable models Lee [41] Brainstem, cerebellum MR McIntosh [42] Corpus callosum MR Szekely [57] Multi-structure MR McInerney [92] Corpus callosum, cerebellum MR Geometric deformable models Shen [24] Hippocampus MR T1 Zhao [27] Hippocampus MR Ghanei [37] Hippocampus MR Leventon [43] Corpus callosum MR Yang [58] Multi-structure MR Tsai [59] Ventricle, caudate nuclei, lenticular nucleus MR Wang [94] Corpus callosum, basal ganglia, ventricle boundaries MR Duncan [95] Hippocampus MR T1 Bekes [96] Eyeballs, lens, nerves CT Machine learning. ANN Hult [25] Hippocampus MR T1, T2 Magnotta [60] Corpus callosum, putamen, caudate nuclei MR T1, T2 Powell [61] Multi-structure MR T1, T2, PD Pierson [62] Cerebellar subregions MR T1, T2 Spinks [99] Thalamus, mediodorsal nucleus MR T1, T2, PD Moghaddam [100] Putamen, caudate, thalamus MR T1…”
Section: Structures Image Modalitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Parametric deformable models Lee [41] Brainstem, cerebellum MR McIntosh [42] Corpus callosum MR Szekely [57] Multi-structure MR McInerney [92] Corpus callosum, cerebellum MR Geometric deformable models Shen [24] Hippocampus MR T1 Zhao [27] Hippocampus MR Ghanei [37] Hippocampus MR Leventon [43] Corpus callosum MR Yang [58] Multi-structure MR Tsai [59] Ventricle, caudate nuclei, lenticular nucleus MR Wang [94] Corpus callosum, basal ganglia, ventricle boundaries MR Duncan [95] Hippocampus MR T1 Bekes [96] Eyeballs, lens, nerves CT Machine learning. ANN Hult [25] Hippocampus MR T1, T2 Magnotta [60] Corpus callosum, putamen, caudate nuclei MR T1, T2 Powell [61] Multi-structure MR T1, T2, PD Pierson [62] Cerebellar subregions MR T1, T2 Spinks [99] Thalamus, mediodorsal nucleus MR T1, T2, PD Moghaddam [100] Putamen, caudate, thalamus MR T1…”
Section: Structures Image Modalitiesmentioning
confidence: 99%
“…According to the type of shape representation used to define the model, DM methods can be categorized in: parametric or explicit deformable models [23,41,42,57,91,92] and geometric or implicit deformable models [27,37,43,58,59,[93][94][95][96][97][98].…”
Section: Deformable Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bekes et al . (4) proposed a geometric model-based method for semi-automatic segmentation of the eye balls, lenses, optic nerves and optic chiasm in CT images and reported quantitative sensitivity and specific results from SRAPLE (5) of approximately 77% and 94% for the chiasm. Qualitatively, Bekes et al reported a lack of consistency among human raters and with the results they obtain for the nerves and chiasm.…”
Section: Introductionmentioning
confidence: 99%
“…However, current segmentation procedures often require manual intervention due to anatomical and imaging variability. Bekes et al 4 proposed a geometric model-based method for semiautomatic segmentation of the eye balls, lenses, ONs, and optic chiasm in computed tomography (CT) images and reported quantitative sensitivity and specificity results from simultaneous truth and performance level estimation (STAPLE) 5 of ∼77%. Qualitatively, this study reported a lack of consistency with the results they obtain for the nerves and chiasm.…”
Section: Introductionmentioning
confidence: 99%